Genome‐wide association study to identify genetic loci associated with gastrointestinal nematode resistance in Katahdin sheep - Becker, G. M. (Anim Genet, 2020)
Resistance to gastrointestinal nematodes has previously been shown to be a moderately heritable trait in some breeds of sheep, but the mechanisms of resistance are not well understood. Selection for resistance currently relies upon faecal egg counts (FEC), blood packed cell volumes and FAMACHA visual indicator scores of anaemia. Identifying genomic markers associated with disease resistance would potentially improve the selection process and provide a more reliable means of classifying and understanding the biology behind resistant and susceptible sheep. A GWAS was conducted to identify possible genetic loci associated with resistance to Haemonchus contortus in Katahdin sheep. Forty animals were selected from the top and bottom 10% of estimated breeding values for FEC from a total pool of 641 sires and ram lambs. Samples were genotyped using Applied Biosystems™ Axiom™ Ovine Genotyping Array (50K) consisting of 51 572 SNPs. Following quality control, 46 268 SNPs were included in subsequent analyses. Analyses were conducted using a linear regression model in plink v1.90 and a single‐locus mixed model in snp and variation suite. Genome‐wide significance was determined by a Bonferroni correction for multiple testing. Using linear regression, loci on chromosomes 2, 3, 16, 23 and 24 were significantly associated at the genome level with FEC estimated breeding values, and we identified a region on chromosome 2 that was significant using both statistical analyses. We suggest a potential role for the gene DIS3L2 for gastrointestinal nematode resistance in Katahdin sheep, although further research is needed to validate these findings.